Contribution of traditional Date palm (Phoenix sylvestris) agroforestry in income generation and livelihood improvements: A case of Jashore district, Bangladesh - Mondol, M.A.; Alam, N. E. K.; Islam, K. K. (International Journal of Environment, Agriculture and Biotechnology, 2021)
Products and services provided by the agroforestry production systems support the basic needs and enhance the livelihood of millions of farmers throughout the world. The benefit of the traditional agroforestry systems and their livelihood improvement strategies are, however, often not systematically addresses in Bangladesh. Thus, the objective of the study was to assess the impact of traditional agroforestry on income generation and livelihood capital development of the rural farmers in Bangladesh. The study selected one of the most common and popular Date palms ((Phoenix sylvestris) agroforestry cases practiced in the Jashore region of Bangladesh. The findings indicated that the most common important feature of the Date palm-based agroforestry system was to generate income and diversified products for the rural farmers. In addition, the physical, financial and natural capital developments were a strong indication of the livelihood developments of farmers. However, the social and human capital development was not satisfactory and this urges an immediate intervention from the government and regional levels. The scientific training on agroforestry and local conflict resolution mechanism process from the government levels would be boosted up the income generation and livelihood development of the farmers in the study area. Therefore, the study recommends to minimize constraints of the agroforestry production systems through training and also enhance social relationship through government official interference would be very effective to make the Date palm agroforestry a more sustainable land-use practice in Bangladesh.